Symptom Duration is not Related to Central Sensitization Inventory in Midportion Achilles Tendinopathy - Morgan N. Potter; Hayley Powell Smitheman; Katie Butera; Ryan T. Pohlig; Karin Grävare Silbernagel (International Journal of Sports Physical Therapy)
# Background